Crystal structure, Hirshfeld surface, DFT, molecular docking of 1-[(6-tert-butyl-2-oxo-2H-chromen-4-yl)methyl]-4,4-dimethylpiperidine-2,6-dione and cytotoxic effects on breast cancer (MDA-MB 231), human alveolar basal epithelial (A549) cell lines - M. Sunitha Kumari; M. Harish Kumar; D. V. Deevith; H. C. Devarajegowda; B. S. Palakshamurthy (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, C21H25NO4, was synthesized by SN2 reaction of bromomethyl coumarin with 4,4-dimethylpiperidine-2,6-dione. The molecule crystalizes in the monoclinic system with space group C2/c. The coumarin unit is almost planar with a dihedral angle between the aromatic rings of 0.81 (2)° and an r.m.s deviation of 0.042 Å. The piperidine ring adopts a chair conformation with the two methyl groups, one methyl group occupying an axial position and the other an equatorial position, exhibiting maximum stability. In the crystal, C—H...O interactions lead to the formation of head-to-head dimers with an R22(8)graph-set motif and R21(9) and R22(10) ring motifs along [001] and [100]. π–π interactions [centroid–centroid distances = 3.885 (2) and 3.744 (2) Å] are also observed. A Hirshfeld surface analysis was carried out, with the two-dimensional fingerprint plots indicating that the major contributions to the crystal packing are from H...H(57%), O...H(29.3%) and C...H(8.1%) interactions. The energy framework calculations reveal that dispersion energy (Edis= −267.7 kJ mol−1) dominates the other energies. The molecular structure was optimized by density functional theory calculations using the B3LYP/6–311+G(d,p) basis set. The HOMO and LOMO orbitals were generated to determine the energy gap, which is 4.245 eV. Molecular docking studies were carried out for the title molecule as ligand and a protein as receptor giving binding affinities of −9.5 kcal mol−1 for PDB ID: 5HG8 and −8.2 kcal mol−1 for PDB ID:6 NLV. The compound was further subjected to biological studies against human cancer cell lines, namely cryopreserved triple negative human breast adenocarcinoma cells (MDA-MB-231cells) and adenocarcinomic human alveolar basal epithelial cells (A549 cells) giving IC50values of 11.57 and 9.34 µM, respectively. The cytotoxicity results showed a good safety profile against HEK293 cell lines.